Is talk always silver and silence golden? - Spörer-Wagner, Doreen (Javnost (Ljubljana), 2010)
Political negotiators require privacy instead of publicity to achieve compromises. Triggered by the spread of governance and the media's increasing relevance to the legitimation of political decisions, democratic negotiators face challenging bargaining conditions in terms of publicity. This applies particularly to political systems whose decision-making relies on majority- rather than on consensusbuilding. In this article we raise the question whether and how bargaining officials perceive and respond to media scrutiny. By referring to negotiators' media-related thinking, we introduce the concept of mediatised negotiation which goes beyond the traditional understanding of mediatisation as an impact on political processes and outcomes. Based on interviews with 32 German political negotiators, it is shown that bargaining officials have an increased awareness of simultaneous negotiation and media management. Even though a set of (in)formal measures is available to cope with this twofold challenge, ineffective and selfish public communication by individual negotiators proved to pose major obstacles to bargaining, not caused but facilitated and intensified by media reporting. We conclude, therefore, that the mediatisation of negotiations is for the most part negotiators' self-mediatisation.
Keywords: politics; politika; communication; komuniciranje; politične komunikacije; pogajanja; javnost; mediji; communication medium